Relationship in the Context of Sustainable Development - Margareta Timbur; Spiridon Pralea (CES Working Papers, 2013)
The overall aim of this paper lies on presenting a short pragmatic image of the main aspects concerning the impact of international trade on the environment, on the one hand, and the impact of environmental policies and regulations on the international trade, on the other hand. Also, this article examines the multilateral environmental agreements (MEAs) focused on the use of environmental trade measures. In the same context, we discuss about the most important international institution with the regulatory powers in international trade – environment relationship which is considered to be GATT/WTO. Although, the international trade-environment relationship is a very debated internationally, in Romania it is not sufficiently addressed either theoretical or practical. Taking into account the transition period and the consequences of the global economic crisis which still will affect Romania a period of time; our country promotes simultaneous strengthening and optimizing of trade and environmental policies in sustainable development framework.
Keywords: F18; Q34; Q56; Q57; 330; eco-friendly goods; eco-label; environment; environmental standards; GATT/WTO; international trade; multilateral environmental agreements; trade liberalization Romania